(untitled) (Bangladesh Journal of Medical Microbiology, 2011)
The present study was conducted to observe the antibiotic sensitivity pattern of isolated S. saprophyticus from urine samples of patients admitted in inpatient department or visited the out patient department of Sir Salimullah Medical College & Mitford Hospital (SSMC& MH) Dhaka from October 2002 to September 2003. Among the isolates, Esch.coli was the most predominant (82.61%) urinary pathogens followed by S. saprophyticus (7.01%). 93.10% S.saprophyticus was isolated from females of which highest (44.82%) rate of isolation was among female of 18- 45 years age group. Rate of isolation was also high (41.38%) among female of <18 years age group. All strains of S.saprophyticus (100%) were sensitive to Imipenem. High sensitivity was also observed to gentamicin (86.20%) andceftriaxone (72.41%). Ciprofloxacin was found to be sensitive against 68.96% isolates. Sensitivity of ceftazidime, cephalexin and cloxacillin were 65.51%, 55.17% and 55.17% respectively. However, most of the S. saprophyticus are resistant to ampicillin, nalidixic acid and cotrimoxazole. So, the present study illustrates that physicians and microbiologists must be aware that S. saprophyticus is an important cause of UTIs in young women and there is a need for continuous evaluation of common antibiotics used in the therapy of uropathogens. DOI: http://dx.doi.org/10.3329/bjmm.v5i1.15817 Bangladesh J Med Microbiol 2011; 05 (01): 21-25